Ovine trophoblasts express cathelicidin host defence peptide in response to infection. (September 2016) - Coyle, Christopher; Wheelhouse, Nick; Jacques, Maxime; Longbottom, David; Svoboda, Pavel; Pohl, Jan; Duncan, W. Colin; Rae, Michael T.; Barlow, Peter G.
Highlights: Expression of Cationic Host Defence Peptides (CHDP) in ovine trophoblasts was characterised. Cells were treated with LPS, the pathogen Waddlia chondrophila, or Vitamin D3. Ovine trophoblasts were found to express genes for cathelicidins. Ovine trophoblasts can differentially express CHDP in response to infection. Unlike human trophoblasts, ovine trophoblasts do not respond to vitamin D3. Abstract: Cationic host defence peptides (CHDP; also known as antimicrobial peptides) are key components of the immune response in the female reproductive tract. The role of the placental trophoblast in ovine host defence remains poorly understood. This study characterises expression of genes for cathelicidin and defensin peptides in primary ovine placental tissues, the ovine trophoblast cell line (AH-1) and in response to the TLR-4 ligand LPS, the abortifacient organism Waddlia chondrophila and 1α, 25-dihydroxyvitamin D3 . Using RT-PCR, expression of the CHDP SMAP-29, sBD-1 and sBD-2 was assessed in the AH-1 cell line in response to LPS, 1α, 25-dihydroxyvitamin D3 exposure (a known stimulator of cathelicidin gene expression), or W. chondrophila infection. Expression of cathelicidin in the trophoblast compartment of the ovine placenta and in the ovine trophoblast cell line (AH-1) was also established. AH-1 cells did not upregulate expression of CHDP in response to LPS, but sBD-1 and sBD-2 expression was significantly increased in response to W. chondrophila infection. SMAP-29 expression was not altered by in vitro exposure to 1α, 25-dihydroxyvitamin D3 . This study demonstrates that the ovine trophoblast expresses cathelicidins, but does not upregulate expression of CHDP in response to LPS. Ovine trophoblasts are shown to differentially regulate expression of CHDP and lack a demonstrable vitamin D-mediated cathelicidin response.